Productive chain of the wool of ewe in the textile sector and confections - Tinoco Gómez, Óscar (2009)
Peru presents production of sheep in all departments. The natural fiber obtained from sheep allows for various textile and garment patterns. This is not reflected significantly in a commercial presence such products. In the domestic market for products derived from sheep’s wool garments are geared primarily to artisanal origin as sweaters, scarves, whereas in the presence of foreign market exports is very small. The value chain approach allows a systemic view of the problem and seek to chain the different elements that compose it. The production chain wool marked three phases: in the primary sector, there are the producers and assemblers, as well as health care, Once sheared, the wool becomes characteristic of the industry processes, such as washing, carded, combed and brushed semi, so you have yarn, fabric based on wool, which can pass through the manufacturing and become the object of textile products and apparel. Finally, marketers involved, both for the domestic market and for export.